An analysis of physicians' diagnostic reasoning regarding pediatric abusive head trauma. (July 2022) - Hymel, Kent P.; Boos, Stephen C.; Armijo-Garcia, Veronica; Musick, Matthew; Weeks, Kerri; Haney, Suzanne B.; Marinello, Mark; Herman, Bruce E.; Frazier, Terra N.; Carroll, Christopher L.; Even, Katelyn; Wang, Ming; et al.
Abstract: Background: Physician diagnoses of abusive head trauma (AHT) have been criticized for circular reasoning and over-reliance on a "triad" of findings. Absent a gold standard, analyses that apply restrictive reference standards for AHT and non-AHT could serve to confirm or refute these criticisms. Objectives: To compare clinical presentations and injuries in patients with witnessed/admitted AHT vs. witnessed non-AHT, and with witnessed/admitted AHT vs. physician diagnosed AHT not witnessed/admitted. To measure the triad's AHT test performance in patients with witnessed/admitted AHT vs. witnessed non-AHT. Participants and setting: Acutely head injured patients <3 years hospitalized for intensive care across 18 sites between 2010 and 2021. Methods: Secondary analyses of existing, combined, cross-sectional datasets. Probability values and odds ratios were used to identify and characterize differences. Test performance measures included sensitivity, specificity, and predictive values. Results: Compared to patients with witnessed non-AHT ( n  = 100), patients with witnessed/admitted AHT ( n  = 58) presented more frequently with respiratory compromise (OR 2.94, 95% CI: 1.50–5.75); prolonged encephalopathy (OR 5.23, 95% CI: 2.51–10.89); torso, ear, or neck bruising (OR 11.87, 95% CI: 4.48–31.48); bilateral subdural hemorrhages (OR 8.21, 95% CI: 3.94–17.13); diffuse brain hypoxia, ischemia, or swelling (OR 6.51, 95% CI: 3.06–13.02); and dense, extensive retinal hemorrhages (OR 7.59, 95% CI: 2.85–20.25). All differences were statistically significant ( p  ≤ .001). No significant differences were observed in patients with witnessed/admitted AHT (n = 58) vs. patients diagnosed with AHT not witnessed/admitted ( n  = 438). The triad demonstrated AHT specificity and positive predictive value ≥0.96. Conclusions: The observed differences in patients with witnessed/admitted AHT vs. witnessed non-AHT substantiate prior reports. The complete absence of differences in patients with witnessed/admitted AHT vs. physician diagnosed AHT not witnessed/admitted supports an impression that physicians apply diagnostic reasoning informed by knowledge of previously reported injury patterns. Concern for abuse is justified in patients who present with "the triad." Highlights: Comparative analyses of patients with admitted/witnessed AHT vs. witnessed non-AHT confirm prior reports. Analyses comparing patients with admitted/witnessed AHT vs. physician-diagnosed AHT serve to refute criticisms of physicians' diagnostic reasoning. The constellation of findings known as "the triad" is both highly specific and predictive of AHT.